Dopamine is a novel, direct inducer of catagen in human scalp hair follicles in vitro. (12th December 2012) - Langan, E.A.; Lisztes, E.; Bíró, T.; Funk, W.; Kloepper, J.E.; Griffiths, C.E.M.; Paus, R.
Summary Background Although there are clinical reports of hair loss associated with levodopa and dopamine agonists, it is unclear whether dopamine exerts any direct effects on the human hair follicle (HF). Objectives Given the widespread use of dopamine agonists and antagonists in clinical medicine, we sought to determine whether dopamine exerts direct effects on human HF growth and/or pigmentation in vitro, and whether human HFs express dopamine receptors (DRs). Methods Microdissected human scalp HFs from women were treated in serum‐free organ culture for 7 days with dopamine (10–1000 nmol L−1), and the effects on hair shaft production, HF cycling (i.e. anagen–catagen transition), hair matrix keratinocyte proliferation and apoptosis, and HF pigmentation were measured by quantitative (immuno‐) histomorphometry. Results Dopamine had no consistent effect on hair shaft production, but did promote HF regression (catagen). It was also associated with significantly reduced proliferation of HF matrix keratinocytes (P < 0·01) and reduced intrafollicular melanin production. Dopamine receptor transcripts were identified in HFs and skin. Conclusions These data provide evidence that dopamine is an inhibitor of human hair growth, via the promotion of catagen induction, at least in vitro. This may offer a rational explanation for the induction of telogen effluvium in some women treated with dopamine agonists such as bromocriptine. Moreover, dopaminergic agonists deserve further exploration as novel inhibitors of unwanted human hair growth (hirsutism, hypertrichosis).